2021
DOI: 10.1177/2158244020981064
|View full text |Cite
|
Sign up to set email alerts
|

Operating Performance of Tourism Listed Companies in China: The Perspective of Economic Value Added

Abstract: This article uses economic value added (EVA) to analyze the sustainability of performance of tourism listed companies from 2013 to 2015. The Malmquist index is used for the analysis of different operating performance across various types of tourism listed companies. It is found that the operating performance of tourism listed companies in China is not satisfactory, as merely less than half of them have a positive EVA. This study also finds that for different types of tourism listed companies, a variety of stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 12 publications
1
14
0
3
Order By: Relevance
“…The modern theory of finance recommends that financial management aims to create value and wealth for shareholders, as advocated by Behera (2020). At the same time, the international literature (Galankashi et al , 2020; Geng et al , 2021) maintains that various efforts have been made to develop performance assessment tools that can and should be effectively used to compare of organizational results of companies and industries in a holistic and sustainable view, also considering that this is a central topic in financial analysis in developed and developing economies.…”
Section: Methodsmentioning
confidence: 99%
“…The modern theory of finance recommends that financial management aims to create value and wealth for shareholders, as advocated by Behera (2020). At the same time, the international literature (Galankashi et al , 2020; Geng et al , 2021) maintains that various efforts have been made to develop performance assessment tools that can and should be effectively used to compare of organizational results of companies and industries in a holistic and sustainable view, also considering that this is a central topic in financial analysis in developed and developing economies.…”
Section: Methodsmentioning
confidence: 99%
“…Some researchers (O'Byrne 2016; Daraban 2018; Jankalová and Kurotová 2020) revealed that EVA differs from other traditional performance values (such as gain per share, gross operating surplus, and return on sales), as it measures all company administration costs (operational costs and funding costs) and focuses on the control of production time, as well as operational and capital costs. Others report that EVA is an efficient measure for evaluating performance, as it: (a) involves all used resources and decentralizes management decision-making (Morard and Balu 2010;Malichova et al 2017); (b) neutralizes differences in the level of risk of each strategic business unit (Mocciaro Li Destri et al 2012); improves the quality of decisions taken at the managerial level, which facilitates the harmonization of interests of parties involved in the creation of value (Hasani and Fathi 2012); allows the performance of such managerial functions as monitoring, planning and signaling of strategic changes (Alam and Nizamuddin 2012); is useful to both shareholders (for measuring real performance) and potential investors (in selecting investment opportunities) (Novyarni and Ningsih 2020); is a relatively mature tool for evaluating listed companies (Geng et al 2021); and, reflects the true economic profit of a business (Orazalin et al 2019).…”
Section: State Of the Art Regarding Evamentioning
confidence: 99%
“…Recent research that is based on the use of EVA as a performance measurement tool has resulted in analyzes being performed on a single company (Wang and Yang 2014;Ion and Man 2019;Jankalová and Kurotová 2020;Novyarni and Ningsih 2020;Radneantu et al 2010) or in sample-level analyzes (Pavelková et al 2018;Geng et al 2021). From the point of view of the analyzed field of activity, these studies focused on various fields, such as: tourism and hotel industry (Trandafir 2015;Geng et al 2021), construction (Horak et al 2020) oil industry (Wang and Yang 2014), steel industry (Ion and Man 2019), banking industry (Owusu-Antwi et al 2015), IT sector (Radneantu et al 2010), and the sale of spare parts (Jankalová and Kurotová 2020). The conclusions of this research are very diverse.…”
Section: State Of the Art Regarding Evamentioning
confidence: 99%
See 2 more Smart Citations